Transcription-coupled nucleotide excision repair factors promote R-loop-induced genome instability - Sollier, Julie; Stork, Caroline Townsend; García-Rubio, María L; Paulsen, Renee D; Aguilera, Andrés; Cimprich, Karlene A (Molecular cell, 2014)
R-loops, consisting of an RNA-DNA hybrid and displaced single-stranded DNA, are physiological structures that regulate various cellular processes occurring on chromatin. Intriguingly, changes in R-loop dynamics have also been associated with DNA damage accumulation and genome instability; however, the mechanisms underlying R-loop-induced DNA damage remain unknown. Here we demonstrate in human cells that R-loops induced by the absence of diverse RNA processing factors, including the RNA/DNA helicases Aquarius (AQR) and Senataxin (SETX), or by the inhibition of topoisomerase I, are actively processed into DNA double-strand breaks (DSBs) by the nucleotide excision repair endonucleases XPF and XPG. Surprisingly, DSB formation requires the transcription-coupled nucleotide excision repair (TC-NER) factor Cockayne syndrome group B (CSB), but not the global genome repair protein XPC. These findings reveal an unexpected and potentially deleterious role for TC-NER factors in driving R-loop-induced DNA damage and genome instability.